P148 Making sense of patient-reported currently treated asthma using routinely collected data. (15th November 2016) - Sallakh, MA Al; Rodgers, SE; Lyons, RA; Sheikh, A; Davies, GA
Abstract : Introduction and objectives: Currently treated asthma (CTA) is commonly assessed in epidemiological studies and is typically self-reported. We investigated how patient understanding of this label compared with objective measures extracted from routinely collected data. Methods: We used the Welsh Health Survey 2014 results for individuals aged 16+. Self-reported CTA was measured with the question: "Are you currently being treated for asthma?" We included those who had valid responses, are record-linked to the Secure Anonymised Information Linkage databank, and had complete GP practice registrations between 2009 and 2014. From the GP dataset, we queried their most recent prescriptions, if any, and whether they had ever recorded asthma diagnosis, and cross-tabulated these variables with self-reported CTA. We examined the concordance between self-reported CTA and each of 'ever prescriptions', 'ever diagnosis', and 'having prescriptions in varying backward intervals from mid-2014', with the latter repeated by adding 'ever diagnosis'. Results: Of 4, 291 eligible people, 10.2% self-reported CTA but, of these, 11.2% had no prescriptions in the past 12 months and 22.4% had no recorded asthma diagnosis ever. Figure 1A shows full intersections between the variables. For concordance between self-reported CTA and each of 'ever prescriptions' and 'ever diagnosis', Cohen's kappa was 0.42 and 0.68, respectively. For concordance between self-reported CTA and 'prescriptions in backward intervals', kappa was 0.76 for the 12-month interval but peaked to 0.77 at 9-months. After adding 'ever diagnosis', the kappa became 0.78 for the 12-month measure (which represents the treated asthma criteria of the Quality of Outcomes Framework, QOF), and peaked to 0.79 at 18-months (Figure 1B ). Conclusion: In Wales, self-reported currently treated asthma showed good concordance with the QOF treated asthma criteria but a slightly better concordance with 'any prescriptions in the last 18 months and ever diagnosis' measured from routine GP data. However, the concordance remains suboptimal, demonstrating that self-reported CTA should be used with caution, and objective measures from routinely collected health data are preferred.